Effect of raw spacing and rate of applied nitrogen on the productivity of signal grass (Brachiaria decumbens stapf) - Okeagu, M.U.; Agishi, E.C. (1990)
This study was conducted to establish parameteres on the optimum spacing and level of nitrogen required for the establishment of most cultivated grass pastures including Brachiaria decumbens. It was found that 20x20 cm spacing of rooted sprigs of signal grass and either 100 or 200 kg N ha were significantly better than either 40x20 cm or 60x20 cm spacing at the same rate of second year (1983). In the third year (1984) however, forage production from the three row spacings was almost the same, differences in production within treatments being largely due to rate of N application